(untitled) (Research, Society and Development, 2021)
Cervical cancer (CCU) is considered a public health problem in developing countries, showing high rates of mortality from this pathology among women of low socioeconomic status and in different reproductive periods of their lives. This article aims to obtain results from data elaborated through research already published on the subject, in which researchers are a key tool in understanding and explaining the problem-question. To carry out the article, a bibliographic review of the integrative literature review type was carried out – the search took place during the month of May 2021. For the selection of studies, an online search was performed in journals and in the following databases: Scientific Electronic Library Online (SciELO), Ministry of Health and National Cancer Institute (INCA). The search for materials resulted in the selection of 22 articles, and after careful reading, 15 articles were selected and used in this research, which met the study proposal. It is essential that nurses appreciate and be engaged in the evolution of care, so that there is a change in mechanistic models, which focus only on the disease, and start to defend and provide care in a humanized, welcoming, empathetic, responsible and resolute manner. Valuing the woman as a whole, considering and understanding her experiences, seeking an exchange of knowledge making the environment comfortable and carrying out nursing guidelines as close as possible to the reality in which the user is inserted, so that there is greater likelihood of follow-up and resolution.